2020
DOI: 10.1007/s00109-020-01937-4
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular karyotyping and gene expression analysis in childhood cancer patients

Abstract: The genetic etiology of sporadic childhood cancer cases remains unclear. We recruited a cohort of 20 patients who survived a childhood malignancy and then developed a second primary cancer (2N), and 20 carefully matched patients who survived a childhood cancer without developing a second malignancy (1N). Twenty matched cancer-free (0N) and additional 1000 (0N) GHS participants served as controls. Aiming to identify new candidate loci for cancer predisposition, we compared the genome-wide DNA copy number variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Given the contradictory roles of SGF29 in cancers, it is worth initiating further studies. ZCWPW2 (zinc finger CW-type PWWP domain protein 2), which is the reader of H3K4me3 ( Danuta et al, 2020 ), was identified as an antioncogene in our study. Until now, the functions of ZCWPW2 in tumors have not been fully studied.…”
Section: Discussionmentioning
confidence: 65%
“…Given the contradictory roles of SGF29 in cancers, it is worth initiating further studies. ZCWPW2 (zinc finger CW-type PWWP domain protein 2), which is the reader of H3K4me3 ( Danuta et al, 2020 ), was identified as an antioncogene in our study. Until now, the functions of ZCWPW2 in tumors have not been fully studied.…”
Section: Discussionmentioning
confidence: 65%
“…Finally, it has been shown that the Ntan1 gene performs numerous functions in vertebrates and defects in the gene can have serious effects at the level of the organism. Thus, alterations in the Ntan1 gene expression have been associated with different types of memory and social behavior 32 , 33 , sporadic childhood cancer 34 and risk of schizophrenia 35 . Therefore, studies in Drosophila using all the new tools available achieve a greater projection in determining the cellular basis of these phenotypes, which is necessary for their possible reversion.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ZNF133 have also been detected in irradiated fibroblasts and in childhood cancer survivors that developed second primary cancer. This overexpression was linked to copy number variation events [ 132 ]. ZNF133 was also recognized as a factor associated with Alagille syndrome—a genetic disease related to the disruptions in the Notch signaling pathway that predisposes to pediatric HCC [ 133 ].…”
Section: Krab-zfps Roles In Cancer Cellsmentioning
confidence: 99%